2013
DOI: 10.1021/ie302839v
|View full text |Cite
|
Sign up to set email alerts
|

Novel Multiscale Control Scheme for Nonminimum-Phase Processes

Abstract: Nonminimum-phase (NMP) processes are frequently encountered in chemical plants, where the presence of right half-plane zeros and time delays often imposes limitations on the achievable control performance. In this article, a new multiscale control scheme for controlling NMP processes is introduced. The novelty of the proposed scheme is to decompose a given plant into a sum of basic factors/modes having distinct speeds of responses. Then, an individual subcontroller is specifically designed to control each of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…The details of multi-scale control (MSC) scheme can be found in [14][15][16][17]. A brief overview of the MSC scheme is presented.…”
Section: Multi-scale Control Schemementioning
confidence: 99%
“…The details of multi-scale control (MSC) scheme can be found in [14][15][16][17]. A brief overview of the MSC scheme is presented.…”
Section: Multi-scale Control Schemementioning
confidence: 99%
“…An interesting feature of the proposed approach is that both the feedback and feedforward controllers are designed based on the recently proposed multi-scale control (MSC) scheme in [10,11]. The authors in [10,11] demonstrated the use of the MSC scheme in designing a PID controller augmented with a filter.…”
Section: Introductionmentioning
confidence: 99%
“…This new scheme is called the ICD-MSC, and it is based on the MSC scheme recently proposed by Nandong and Zang [24,25] for SISO nonminimum-phase processes. The design principle of the MSC scheme is to first decompose a given plant into a sum of basic modes, each having distinct speed of responses.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the inner feedback loop is faster than the outer feedback loop. Hence, the scheme is called the MSC because of the combination of several sub-controllers with different speeds [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation